Ocean Acidification Triggers Cell Signaling, Suppress Immune and Calcification in the Pacific Oyster Larvae - Dineshram, Ramadoss; Xiao, Shu; Ko, Ginger Wai Kuen; Li, Jun; Smrithi, Kovilingal; Thiyagarajan, Vengatesen; Zhang, Yang; Yu, Ziniu (Frontiers in Marine Science, 2021)
Elevated carbon dioxide levels in ocean waters, an anthropogenic stressor, can alter the chemical equilibrium of seawater through a process called ocean acidification (OA). The resultant reduction of pH can be detrimental during the early developmental stages of the commercially important edible Pacific oyster Crassostrea gigas; the ability of larvae to join a population is likely to be compromised by declining ocean pH. Given this threat, it is important to study the molecular mechanisms that these organisms use to overcome OA stress at the gene expression level. Here, we performed transcriptome profiling in oyster larvae following exposure to ambient (8.1) and reduced (7.4) pH during the pre-settlement growth period (i.e., 18 d post fertilization) using RNA-seq with Illumina sequencing technology. In total, 1,808 differentially expressed genes (DEGs) were identified, 1,410 of which were matched by BLAST against the Swiss-Prot database. Gene ontology classification showed that most of these DEGs were related to ribosomal, calcium ion binding, cell adhesion and apoptotic processes. Pathway enrichment analysis revealed that low pH (7.4) enhanced energy production and organelle biogenesis but prominently suppressed several immune response pathways. Moreover, activation of the MAPK signaling pathway was observed along with inhibition of the Wnt, VEGF and ErbB pathways, highlighting the fact that the initiation of stress responses is given priority over larval development or shell growth when the larvae cope with low pH. In conclusion, our study demonstrated a unique gene expression profiling approach to studying oyster larval responses to OA, which not only provides comprehensive insights into the mechanisms underlying oyster tolerance to CO2-driven decreases in ocean pH but also supplies a valuable genomic resource for further studies in this species.